Electrochemical Polishing of Two-Dimensional Materials - Sebastian, Amritanand; Zhang, Fu; Dodda, Akhil; May-Rawding, Dan; Liu, He; Zhang, Tianyi; Terrones, Mauricio; Das, Saptarshi (ACS nano, 2019)
Two-dimensional (2D) layered materials demonstrate their exquisite properties such as high temperature superconductivity, superlubricity, charge density wave, piezotronics, flextronics, straintronics, spintronics, valleytronics, and optoelectronics, mostly, at the monolayer limit. Following initial breakthroughs based on micromechanically exfoliated 2D monolayers, significant progress has been made in recent years toward the bottom-up synthesis of large-area monolayer 2D materials such as MoS2 and WS2 using physical vapor deposition and chemical vapor deposition techniques in order to facilitate their transition into commercial technologies. However, the nucleation and subsequent growth of the secondary, tertiary, and greater numbers of vertical layers poses a significant challenge not only toward the realization of uniform monolayers but also toward maintaining their consistent electronic and optoelectronic properties which change abruptly when transitioning from the monolayer to multilayer form. Chemical or physical techniques which can remove the unwanted top layers without compromising the material quality will have tremendous consequences toward the development of atomically flat, large-area, uniform monolayers of 2D materials. Here, we report a simple, elegant, and self-limiting electrochemical polishing technique that can thin down any arbitrary thickness of 2D material, irrespective of whether these are obtained using powder vapor transport or mechanical exfoliation, into their corresponding monolayer form at room temperature within a few seconds without compromising their atomistic integrity. The effectiveness of this electrochemical polishing technique is inherent to 2D transition-metal dichalcogenides owing to the stability of their basal planes, enhanced edge reactivity, and stronger than van der Waals interaction with the substrate. Our study also reveals that 2D monolayers are chemically more robust and corrosion resistant compared to their bulk counterparts in similar oxidative environments, which enables electrochemical polishing of such materials down to a monolayer.